ON THE CHRISTIAN ECOLOGICAL IMPERATIVE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article discusses the features of the idea of human dominance over nature, proclaimed in a fairly obvious form in the Bible. Later, as the Christian civilization developed, the Europeans spread the Christian ecological paradigm. At present, mankind largely continues to adhere to this paradigm.
Keywords: ecology, Christian ecological imperative, ecological crisis